EFFECTIVENESS OF TEACHING MATERIAL READING CONTEMPORY CHINESE LITERATURE AND CULTURE-BASED CULTURE WORKS - Biduri, Febi Nur; Rasyid, Yumna (IJLECR (International Journal of Language Education and Cultural Review), 2017)
A research and development of teaching materials will focus on the development of textbook products in accordance with the needs of students, lecturers and also majors. Culture and literature knowledge that has been studied in Mandarin Darma Persada University program is not maximal and in accordance with the needs of students. So to adjust to the needs of these students making these teaching materials using the theme of contextual Chinese and cultural literature-based. To test the effectiveness of the model researchers have conducted experimental teaching materials to read the works of literature and culture-based Mandarin contextual, research conducted using the theory of experimental pre so that only implemented in one class reading 5 faculty of Chinese language and culture of Darma Persada University in academic year 2016/2017 in Jakarta. Respondents of the study were 18 students who had mastered Mandarin well, the results of this study indicate that T count (4.060) is greater than T table (2.101), thus it can be concluded that this significant mean difference means Ho is rejected and H1 be accepted. Thus the teaching material model of reading the literature and culture culture of Mandarin based on contextual is more effective in improving students’ reading skill in semester 5.